Navigating TAM receptor dynamics in tumour immunotherapy - Jihao Yang; Guanmin Chen; Rui Wang; Chengcheng Song; Huaqiang Yi (Cancer Immunology, Immunotherapy)
Abstract The TAM receptor family is getting more and more attention in the field of tumour immunity. Activation of TAM receptors not only aids in the survival and multiplication of tumour cells but also increases their likelihood of invading other cells and spreading. In addition, activation of TAM receptors helps to inhibit the anti-tumour immune response, allowing tumour cells to evade immune surveillance. In terms of therapeutic strategies, a number of inhibitors targeting TAM receptors are in preclinical and clinical development. Despite significant progress in clinical trials in recent years, challenges remain. This review delves into the kinetic characteristics of the TAM receptor family, their dual role in tumour immunity, and the transmission process of downstream signalling pathways. Based on this, we analysed and summarised the unique strategies and combination therapies for regulating tumour immunity using TAM receptor inhibitors. It not only helps to elucidate the key role of TAM receptors in tumour immunity but also provides new perspectives and strategies for future tumour therapy.